A comprehensive survey of multi-view video summarization. (January 2021) - Hussain, Tanveer; Muhammad, Khan; Ding, Weiping; Lloret, Jaime; Baik, Sung Wook; de Albuquerque, Victor Hugo C.
Highlights: The very first survey of multi-view video summarization. Coverage of full literature of multi-view video summarization from 2010 till date. Major challenges of multi-view video summarization in the light of surveyed literature. Coverage and investigation of benchmark datasets for multi-view video summarization. Detailed recommendations for future research. Abstract: There has been an exponential growth in the amount of visual data on a daily basis acquired from single or multi-view surveillance camera networks. This massive amount of data requires efficient mechanisms such as video summarization to ensure that only significant data are reported and the redundancy is reduced. Multi-view video summarization (MVS) is a less redundant and more concise way of providing information from the video content of all the cameras in the form of either keyframes or video segments. This paper presents an overview of the existing strategies proposed for MVS, including their advantages and drawbacks. Our survey covers the genericsteps in MVS, such as the pre-processing of video data, feature extraction, and post-processing followed by summary generation. We also describe the datasets that are available for the evaluation of MVS. Finally, we examine the major current issues related to MVS and put forward the recommendations for future research 1 .